Neotrombicula roubaudi - Stekolnikov, Alexandr A. (Zenodo, 2018)
Neotrombicula roubaudi (Vercammen-Grandjean, 1956) Trombicula (Neotrombicula) roubaudi Vercammen-Grandjean, 1956d: 79, pls 1C–D, 2C–D. Neotrombicula roubaudi – Zumpt 1961: 145. — Goff 1995: 12. Neotrombicula roubaudi roubaudi – Taufflieb 1960a: 46. Neotrombicula (Neotrombicula) roubaudi – Vercammen-Grandjean 1965c: 71. Holotype No data. Material revised Four paratypes from RMCA, not suitable for examination. Distribution Morocco (Oued Cherrat, Tit Mellil). Hosts Apodemus sylvaticus , Dipodillus campestris , Eliomys munbyanus , Lemniscomys barbarus , Mus spicilegus , M. spretus , Mustela nivalis numidica , Oryctolagus cuniculus , Paridae gen. sp., Passeriformes gen. sp., Rattus rattus. : Published as part of Stekolnikov, Alexandr A., 2018, Taxonomy and distribution of African chiggers (Acariformes, Trombiculidae), pp. 1-233 in European Journal of Taxonomy 395 on page 182, DOI: 10.5852/ejt.2018.395, http://zenodo.org/record/3829724 : {"references": ["Vercammen-Grandjean P. H. 1956 d. Les Heaslipia Ewing 1944 et les Neotrombicula Hirst 1915 sont-ils congeneres? Description de cinq Trombiculidae originaires du Maroc. Archives de l'Institut Pasteur du Maroc 5 (4): 75 - 86.", "Zumpt F. (ed.) 1961. The arthropod parasites of vertebrates in Africa south of the Sahara (Ethiopian Region). Vol. 1: Chelicerata. Publications of the South African Institute for Medical Research 11 (50): 1 - 457.", "Goff M. L. 1995. New species of Neotrombicula (Acari: Trombiculidae) from African primates (Galagidae and Cercopithecidae). Journal of Medical Entomology 32 (1): 12 - 15. https: // doi. org / 10.1093 / jmedent / 32.1.12", "Taufflieb R. 1960 a. Contribution a l'etude des Trombiculidae Marocains. Description de nouvelles especes et etude d'une population de Neotrombicula. Archives de l'Institut Pasteur du Maroc 7 (1): 27 - 48.", "Vercammen-Grandjean P. H. 1965 c. Trombiculinae of the World. Synopsis with Generic, Subgeneric, and Group Diagnoses (Acarina, Trombiculidae). George Williams Hooper Foundation, San Francisco."]}